2003
DOI: 10.1038/sj.ijo.0802283
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in weight in perimenopausal and early postmenopausal women: effects of dietary energy intake, energy expenditure, dietary calcium intake and hormone replacement therapy

Abstract: OBJECTIVE:To investigate whether energy intake or energy expenditure affects 5-7 y weight gain in perimenopausal and early postmenopausal women, and whether hormone replacement therapy (HRT) use or dietary calcium (Ca) intake are contributory factors. DESIGN: Longitudinal, observational study of healthy women around the menopause. SUBJECTS: A total of 1064 initially premenopausal women, selected from a random population of 5119 women aged 45-54 y at baseline. In all, 907 women (85.2%) returned 6.370.6 y later … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
2
9

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(68 citation statements)
references
References 32 publications
7
50
2
9
Order By: Relevance
“…This investigation examined 5-year change in diet in 898 perimenopausal and early postmenopausal women. We previously reported no difference in weight change between the groups 16 . Some changes in food patterns over 5 years were observed but changes in nutrient intakes were small.…”
Section: Discussionmentioning
confidence: 86%
“…This investigation examined 5-year change in diet in 898 perimenopausal and early postmenopausal women. We previously reported no difference in weight change between the groups 16 . Some changes in food patterns over 5 years were observed but changes in nutrient intakes were small.…”
Section: Discussionmentioning
confidence: 86%
“…These results may be interpreted in three different ways: (a) physical activity is an important factor in preventing weight gain, but the true association is not detectable because of measurement error; (b) less weight gain leads to better exercise adherence; a reverse causality argument; (c) the self-reported physical activity may be a proxy for a general healthy lifestyle; a confounding argument. In the current review an additional fourteen observational studies on physical activity and weight gain in adults have been identified, of which only two have included an objective measure to assess physical activity (Tataranni et al 2003;Ekelund et al 2005), whereas the other twelve studies have assessed physical activity by means of self-report (Rainwater et al 2000;Schmitz et al 2000;Sherwood et al 2000;Bell et al 2001;Wagner et al 2001;Ball et al 2002;Hu et al 2003;Koh-Banerjee et al 2003;Macdonald et al 2003;Droyvold et al 2004;Petersen et al 2004;Wenche et al 2004).…”
Section: Cohort Studies In Adultsmentioning
confidence: 99%
“…The mean weight of the women had increased (independent of menopausal status) 33 . This could not be explained by an increase in food consumption since energy and total fat intakes had decreased significantly (albeit slightly) in most of the hormonal groups and, overall, the diet had not changed significantly for the majority of women 34,35 . However, physical activity levels (as assessed by measurement of physical activity level, PAL) had decreased in the majority of women.…”
Section: Bone Health In Adolescent Girls and Boysmentioning
confidence: 88%
“…Papers have been published (Macdonald et al, 2001a(Macdonald et al, , 2001b and more have been submitted (Macdonald et al, 2002a(Macdonald et al, , 2002b(Macdonald et al, , 2002c(Macdonald et al, , 2002d). …”
Section: Appendix B -Projects Commissioned In Phase 21 Of the Nutritmentioning
confidence: 99%